Construcción de Estrategias Sistemáticas para la Busqueda Exhaustiva de Información en Internet: un marco de toma de decisiones aplicado a la información sobre Psicología de la Salud. - Julio Meneses; Merce Boixadós; Lourdes Valiente; Pep Vivas; Manuel Armayones (Information Research: An International Electronic Journal)
With the progressive increase of publicly available contents on the Internet and as information searching has become one of the most frequent online activities, informal and common searching cannot respond to the aims of scientific research. In regard to the relevant contents in a specific field of knowledge in a non-organised environment such as the Internet, the need of developing efficient procedures to guarantee a systematic search process arises. The development of these procedures or strategies, articulated by means of the properties of exhaustiveness in the search process, replicability of the procedure and ecologic validity, not only is not it arbitrary, but it is directly related to the time spent in the carrying out of the process and the quality of the resulting information. After the critical review of the different alternatives in information seeking, the current article intends to suggest a framework for this decision making process. Furthermore, the whole process is exemplified by the development of a systematic strategy in the field of the information about Health Psychology.